Angiographic Microvascular Resistance Is an Independent Predictor of Adverse Clinical Outcomes After Transcatheter Aortic Valve Replacement - Wence Shi; Hongliang Zhang; Lei Song; Tongqiang Zou; Lihua Xie; Changdong Guan; Moyang Wang; Yongjian Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The coronary microcirculatory resistance index plays a crucial role in predicting patient prognosis. Coronary angiography‐based methods for assessing coronary microcirculatory function offer advantages such as simplicity and cost‐effectiveness. This study aimed to confirm the prognostic value of a novel angiographic microvascular resistance (AMR) index in patients undergoing transcatheter aortic valve replacement. Methods and Results We prospectively included 335 patients with severe aortic stenosis who underwent transcatheter aortic valve replacement at Fuwai Hospital. The AMR was calculated based on coronary angiography performed before prosthetic valve implantation. Patients were divided into 2 groups based on an AMR cutoff value of 250: AMR ≤250 and AMR >250. The primary end point was major adverse cardiovascular events, defined as a composite of all‐cause mortality, readmission for heart failure, and myocardial infarction. At a median follow‐up of 40 months (interquartile range [IQR], 25–50), AMR was significantly higher in patients who experienced the primary end point (257 [IQR, 186–299] versus 226 [IQR, 177–264]; P<0.001), identifying it as an independent risk factor for major adverse cardiovascular events, all‐cause mortality, and new‐onset atrial fibrillation. Kaplan‐Meier analysis indicated that patients with AMR >250 had significantly lower event‐free survival rates for major adverse cardiovascular events (62.9% versus 75.1%; hazard ratio, 1.94 [95% CI, 1.34–2.81]; log‐rank P<0.001), mainly driven by all‐cause death (75.7% versus 83.4%, log‐rank P=0.018). Subgroup analyses supported these findings for major adverse cardiovascular events. Conclusions AMR is an independent predictor of adverse clinical outcomes after transcatheter aortic valve replacement. An AMR >250 can be used as a novel indicator for long‐term prognostic management.